Electron transport layer based on fluoride treatment, preparation method of electron transport layer and application of electron transport layer in perovskite solar cell

By adopting a fluoride-based electron transport layer in perovskite solar cells, the problem of ion defects in perovskite films is solved, and the efficiency and stability of the device are improved.

CN119562692AInactive Publication Date: 2025-03-04CHANGCHUN INST OF OPTICS FINE MECHANICS & PHYSICS CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411651395.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In existing perovskite solar cells, the polycrystalline perovskite film has a large number of ionic defects, which affects the stability and efficiency of the device.

Method used

Using a fluoride-based electron transport layer, the nucleation process of perovskites is improved and the defects in the film are regulated by introducing fluoride between the electron transport layer and the perovskite optical transport layer.

Benefits of technology

The efficiency and stability of perovskite solar cells are significantly improved, the defect state density is reduced, and non-radiative recombination is suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562692A_ABST
    Figure CN119562692A_ABST
Patent Text Reader

Abstract

The invention relates to an electron transport layer based on fluoride treatment, a preparation method thereof and application of the electron transport layer in a perovskite solar cell, and belongs to the technical field of perovskite solar cells. The technical problem that a large number of ion defects exist on the surface and in the interior of the polycrystalline perovskite thin film in the prior art is solved. The electron transport layer based on fluoride treatment comprises an electron transport layer, the surface of the electron transport layer is treated by fluoride, and the fluoride contains coordination sites. The fluoride is introduced to the electron transport layer, so that the wettability of the perovskite precursor solution on the surface of the electron transport layer is improved, the occurrence of a perovskite nucleation process is promoted, the generation of defects is reduced, and the quality of the perovskite thin film is further improved. In addition, the introduction of the fluoride regulates and controls the defect state density in the electron transport layer and the perovskite thin film, and improves the efficiency and stability of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cells (PSCs), and in particular relates to an electron transport layer based on fluoride treatment and a preparation method thereof and an application thereof in perovskite solar cells. Background Art

[0002] Organic-inorganic metal halide perovskite materials have great potential in optoelectronic device applications due to their high light absorption coefficient, adjustable band gap width, long carrier diffusion length, and low exciton binding energy. Perovskite solar cells (PSCs) have attracted widespread attention from researchers due to their simple preparation process, low preparation cost, and rapidly improving efficiency.

[0003] In recent years, PSCs-related research has developed rapidly, and the performance of devices has been continuously improved. So far, the efficiency of PSCs has exceeded 26%, but the stability problem caused by defects is a key factor limiting the industrialization of PSCs.

[0004] Polycrystalline perovskite films are mostly prepared by solution spin coating, which inevitably produces a large number of ion defects on the surface and inside the film. According to the energy level, defects can be divided into deep energy level defects and shallow energy level defects. The carriers captured by deep energy level defects cannot be re-emitted back to the conduction band or valence band, and will provide sites for non-radiative recombination, thereby losing device performance. Although shallow energy level defects are generally considered benign, they provide channels for the migration of water, oxygen molecules and ions, limiting the improvement of device stability. Summary of the invention

[0005] In view of this, the present invention aims to solve the technical problem in the prior art that a large number of ion defects exist on the surface and inside of a polycrystalline perovskite film, and to provide an electron transport layer based on fluoride treatment, a preparation method thereof, and an application in a perovskite solar cell. The obtained perovskite solar cell has the characteristics of high efficiency and stability.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows.

[0007] The present invention provides an electron transport layer based on fluoride treatment, comprising an electron transport layer, wherein the surface of the electron transport layer is treated with fluoride, and the fluoride contains coordination sites.

[0008] Preferably, the material of the electron transport layer is tin dioxide (SnO2).

[0009] Preferably, the electron transport layer has a thickness of 10 to 100 nm.

[0010] Preferably, the fluoride is selected from any one of the following structures:

[0011]

[0012] The present invention also provides a method for preparing the above-mentioned electron transport layer based on fluoride treatment, and the steps are as follows:

[0013] Dissolve the fluoride in an organic solvent to obtain a mixed solution;

[0014] Deposit the mixed solution on the surface of the electron transport layer and perform annealing treatment to obtain an electron transport layer based on fluoride treatment.

[0015] Preferably, the organic solution is chlorobenzene, isopropanol or ethyl acetate.

[0016] Preferably, in the mixed solution, the concentration of the fluoride is 0.002 - 2 mM.

[0017] Preferably, the deposition method is spin coating, and the rotation speed is 2000 - 4000 rpm; the annealing temperature is 100 - 150 °C, and the annealing time is 3 - 10 min; more preferably, the annealing temperature is 130 - 150 °C, and the annealing time is 3 - 5 min.

[0018] The present invention also provides a perovskite solar cell containing the above-mentioned perovskite film based on fluoride treatment, which includes a substrate, a cathode, an electron transport layer based on fluoride treatment, a perovskite light absorption layer, a hole transport layer and an anode stacked in sequence.

[0019] Preferably, the cathode is fixed on the upper surface of the substrate, and a part of the upper surface of the substrate is exposed. The electron transport layer based on fluoride treatment is fixed on the upper surface of the cathode and the exposed upper surface of the substrate, and a part of the upper surface of the cathode is exposed. The perovskite light absorption layer is fixed on the upper surface of the electron transport layer based on fluoride treatment, the hole transport layer is fixed on the upper surface of the perovskite light absorption layer, and the anode is fixed on the upper surface of the hole transport layer.

[0020] Preferably, the substrate and the cathode are integrally formed and are a transparent conductive glass substrate. More preferably, the transparent conductive glass substrate is an FTO conductive glass, an ITO conductive glass or an AZO conductive glass.

[0021] Preferably, the molecular formula of the material of the perovskite light absorption layer is FA x Cs 1-x PbI3, where 0 < x ≤ 1; the thickness of the perovskite light absorption layer is 300 - 800 nm.

[0022] Preferably, the material of the hole transport layer is Spiro-OMeTAD, PTAA, PEDOT:PSS, SAM or P3HT, and the thickness of the hole transport layer is 20 to 800 nm.

[0023] Preferably, the material of the anode is metal, and more preferably, the metal is one or more of gold, silver, and aluminum; the thickness of the anode is 100-150 nm.

[0024] The present invention also provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:

[0025] Step 1: ultrasonically clean the substrate with the cathode using a cleaning agent, deionized water, acetone, isopropanol, and anhydrous ethanol in sequence, and then dry it;

[0026] Step 2: depositing a solution containing an electron transport layer material onto the surface of the substrate with the cathode after being irradiated by an ultraviolet lamp, and then performing an annealing treatment to obtain an electron transport layer;

[0027] Step 3: dissolving the fluoride in an organic solvent, depositing the obtained mixed solution on the surface of the electron transport layer in step 2, and then performing annealing treatment to obtain an electron transport layer based on fluoride treatment;

[0028] Step 4: depositing a perovskite precursor solution on the surface of the fluoride-based electron transport layer in step 3, followed by annealing to obtain a perovskite light absorption layer;

[0029] Step 5: depositing a solution containing hole transport layer materials on the surface of the perovskite light absorption layer to obtain a hole transport layer;

[0030] Step 6: Prepare an anode on the surface of the hole transport layer.

[0031] Preferably, in step 1, ultrasonic cleaning is performed in a cleaning agent, deionized water, acetone, isopropanol, and anhydrous ethanol for 20 to 30 minutes respectively; more preferably, the water cleaning agent is conductive glass.

[0032] Preferably, in step 2, the ultraviolet lamp irradiation time is 10 to 30 minutes.

[0033] Preferably, in step 2, in the solution containing the electron transport layer material, the concentration of the electron transport layer material is 2-4 wt %.

[0034] Preferably, in step 2, the deposition method is spin coating, the rotation speed is 3000-5000 rpm, the annealing temperature is 150-200° C., and the annealing time is 20-30 min.

[0035] Preferably, in step three, the deposition method is spin coating, and the rotation speed is 2000-4000 rpm; the annealing temperature is 100-150°C, and the annealing time is 3-10 min; more preferably, the annealing temperature is 130-150°C, and the annealing time is 3-5 min.

[0036] Preferably, in step 4, the perovskite precursor solution is deposited on the surface of the fluoride-treated electron transport layer using a one-step anti-solvent method, and the anti-solvent is anhydrous ether, chlorobenzene or ethyl acetate.

[0037] Preferably, in step 4, the preparation method of the perovskite precursor solution is: using cesium iodide (CsI), formamidine hydroiodide (FAI), and lead iodide (PbI2) as solutes, N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP) as a mixed solvent, and then stirring at room temperature and in the dark to obtain FA x Cs 1-x PbI3 perovskite precursor solution;

[0038] More preferably, the volume ratio of N,N-dimethylformamide (DMF) to N-methylpyrrolidone is 4:1 to 6:1;

[0039] More preferably, the concentration of the perovskite precursor solution is 0.5-1.5M.

[0040] Preferably, in step 4, the deposition method is spin coating, and the rotation speed is 3000-5000 rpm; the annealing temperature is 150-200° C., and the annealing time is 20-30 min.

[0041] Preferably, in step 5, the preparation method of the solution containing the hole transport layer material is: dissolving the hole transport layer material in a chlorobenzene solution to obtain a solution containing the hole transport layer material;

[0042] Preferably, in step five, the deposition method is spin coating, the rotation speed is 2000-5000 rpm, and the spin coating time is 20-50 s.

[0043] Preferably, in step six, the anode is prepared by vacuum evaporation technology.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The method for preparing the perovskite film of the present invention improves the nucleation process of the perovskite and improves the quality of the film by introducing fluoride between the electron transport layer and the perovskite light transport layer.

[0046] (2) The fluoride introduced into the perovskite film of the present invention contains multiple coordination sites, which can regulate the defects in the electron transport layer and the perovskite light transport layer, reduce the defect state density, inhibit non-radiative recombination, and improve the film quality.

[0047] (3) The perovskite film of the present invention is applied to perovskite solar cells, which can improve the efficiency and stability of the perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 It is a schematic structural diagram of the perovskite solar cell of the present invention;

[0050] 1. Substrate, 2. Cathode, 3. Fluoride-based electron transport layer, 4. Perovskite light absorption layer, 5. Hole transport layer, 6. Anode.

[0051] Figure 2 1 and 1 are top-view scanning electron microscope images of the perovskite film treated with and without fluoride in the present invention, a being without fluoride treatment and b being with fluoride treatment.

[0052] Figure 3 The UV-visible absorption spectra of the perovskite films treated with and without fluoride in the present invention.

[0053] Figure 4 1 is the XRD diagram of the perovskite film treated with and without fluoride in the present invention.

[0054] Figure 5 Steady-state photoluminescence (left) and time-resolved photoluminescence (right) spectra of the perovskite films treated with and without fluoride in the present invention.

[0055] Figure 6 1 is the current density-voltage curve of the perovskite solar cell with and without fluoride treatment in the present invention.

[0056] Figure 7 The current density-voltage curves of the perovskite solar cells treated with and without fluoride in the present invention under reverse and forward scanning conditions, the left figure is untreated, and the right figure is treated.

[0057] Figure 8The normalized efficiency statistics of unencapsulated perovskite solar cells with and without fluoride treatment after continuous exposure to air environment at room temperature for 3000 hours. DETAILED DESCRIPTION

[0058] The method of the present invention is described below by way of examples. The examples described are merely specific descriptions of the claims of the present invention, and the claims include but are not limited to the contents of the examples described.

[0059] Unless otherwise specified, the reagents and materials described in the following examples can be obtained from commercial sources; the test methods described are conventional methods unless otherwise specified.

[0060] Example 1

[0061] like Figure 1 As shown, this embodiment provides a fluoride-treated perovskite solar cell, comprising a substrate 1, a cathode 2, a fluoride-treated electron transport layer 3, a perovskite light absorption layer 4, a hole transport layer 5 and an anode 6, wherein the cathode 2 is fixed on the upper surface of the substrate 1, and the upper surface of the substrate 1 is partially exposed, the fluoride-treated electron transport layer 3 is fixed on the upper surface of the cathode 2 and the exposed upper surface of the substrate 1, and the upper surface of the cathode 2 is partially exposed, the perovskite light absorption layer 4 is fixed on the upper surface of the fluoride-treated electron transport layer 3, the hole transport layer 5 is fixed on the upper surface of the perovskite light absorption layer 4, and the anode 6 is fixed on the upper surface of the hole transport layer 5. The preparation method thereof comprises the following steps:

[0062] (1) Using a cleaning agent, deionized water, acetone, isopropanol, and anhydrous ethanol, ultrasonically clean the FTO transparent conductive glass substrate for 20 minutes in sequence, dry it, and set it aside;

[0063] (2) Add deionized water to a commercially available SnO2 dispersion with a concentration of 12 wt% to dilute it to 2.67 wt% to obtain a solution containing an electron transport layer material. The solution is dropped onto the surface of a FTO transparent conductive glass substrate, spin-coated at a speed of 3000 rpm for 30 seconds, and then annealed at 150°C for 30 minutes to obtain an electron transport layer;

[0064] (3) dissolving cesium trifluoroacetate in isopropanol solution to a concentration of 0.5 mg / mL, stirring in a closed chamber for 2 h, and spin coating the solution on the surface of the electron transport layer obtained in step (2) at a rotation speed of 3000 rpm, and then annealing at 130° C. for 3 min to obtain a fluoride-treated electron transport layer 2;

[0065] (4) 691.5 mg of PbI2, 252.8 mg of FAI, and 7.8 mg of CsI were dissolved in 1 mL of a DMF / NMP mixed solution (the volume ratio of DMF / NMP was 6:1), and stirred for 12 h in a dark environment to obtain FA 0.98 Cs 0.02 PbI3 perovskite precursor solution;

[0066] (5) Replace the FA in step (4) 0.98 Cs 0.02 The PbI3 perovskite precursor solution is dripped onto the surface of the fluoride-treated electron transport layer 2 obtained in step (3), and the substrate is rotated at a speed of 5000 rpm for 60 seconds. At the 12th second after the start of spin coating, 500 μL of anti-solvent (ethyl acetate) is poured at the center of the substrate to obtain a perovskite precursor film.

[0067] (6) annealing the perovskite precursor film described in step (5) at 150° C. for 20 min to obtain a perovskite light absorbing layer 3;

[0068] (7) 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and then 16.5 μL of Li-TFSI solution (520 mg of Li-TFSI was dissolved in 1 mL of acetonitrile solution) and 28.8 μL of tBP were added in sequence to obtain a solution containing a hole transport layer material;

[0069] (8) Spin coating the solution containing the hole transport layer material described in step (7) on the perovskite light absorption layer 3 prepared in step (6) at a rotation speed of 3000 rpm, and then leaving it in a dry and dark condition for 12 hours to obtain a hole transport layer 4;

[0070] (9) A silver electrode is deposited on the surface of the hole transport layer 4 described in step (8) by thermal evaporation to form an anode 5 with a thickness of 100 nm, thereby obtaining a fluoride-treated perovskite solar cell.

[0071] Comparative Example 1

[0072] The operation of step (3) is not performed, and the perovskite precursor film is directly prepared on the surface of the electron transport layer. The other steps are the same as those in Example 1.

[0073] The FA prepared in Example 1 and Comparative Example 1 0.98 Cs 0.02 The scanning electron microscope top view of the PbI3 perovskite light absorption layer 3 is shown in Figure 2 As shown, it can be seen that the grain size of the perovskite in Example 1 is large and uniform and dense.

[0074] FA prepared in Example 1 and Comparative Example 1 0.98Cs 0.02 The UV-visible absorption spectrum of the PbI3 perovskite light absorbing layer 3 is as follows Figure 3 As shown in the figure, it can be seen that the perovskite light absorption layer 3 prepared in Example 1 exhibits strong light absorption ability in the entire wavelength range of 400 to 800 nm.

[0075] FA prepared in Example 1 and Comparative Example 1 0.98 Cs 0.02 The XRD pattern of the PbI3 perovskite light absorbing layer 3 is shown in Figure 4 As shown in the figure, it can be seen that the perovskite light absorption layer 3 prepared in Example 1 exhibits strong crystallinity.

[0076] FA prepared in Example 1 and Comparative Example 1 0.98 Cs 0.02 The steady-state photoluminescence and time-resolved photoluminescence spectra of the PbI3 perovskite light absorbing layer 3 are shown in Figure 2. Figure 5 As shown, the results show that the carrier extraction ability of the perovskite light absorbing layer 3 prepared in Example 1 is improved.

[0077] The current density-voltage curves of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1 are as follows: Figure 6 As shown, the photoelectric parameter statistics of the current density-voltage curves of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1 are shown in Table 1.

[0078] Table 1 Photoelectric parameters of the current density-voltage curves of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1

[0079]

[0080] from Figure 6 As can be seen from Table 1, the short-circuit current, open-circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell device prepared in Example 1 are significantly improved.

[0081] The current density-voltage curves of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1 under reverse scanning and forward scanning conditions are as follows: Figure 7 As shown, the photoelectric parameter statistics of the reverse scanning and forward scanning current density-voltage curves of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1 are shown in Table 2.

[0082] Table 2 Photoelectric parameters of the reverse scanning and forward scanning current density-voltage curves of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1

[0083]

[0084] from Figure 7 As can be seen from Table 2, the hysteresis effect of the perovskite solar cell device prepared in Example 1 is significantly suppressed.

[0085] The photoelectric conversion efficiency statistics of the unpackaged perovskite solar cell devices prepared in Example 1 and Comparative Example 1 after storage in an air environment for 3000 hours are as follows: Figure 8 As shown. Figure 8 It can be seen that the stability of the perovskite photoelectric device in Example 1 has been significantly improved.

[0086] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. An electron transport layer based on fluoride treatment, characterized in that including an electron transport layer; The surface of the electron transport layer is treated with fluoride, and the fluoride contains coordination sites.

2. The electron transport layer based on fluoride treatment according to claim 1, characterized in that The material of the electron transport layer is tin dioxide; And / or, the thickness of the electron transport layer is 10 to 100 nm.

3. The electron transport layer based on fluoride treatment according to claim 1, characterized in that The fluoride is selected from any one of the following structures:

4. The method for preparing an electron transport layer based on fluoride treatment according to any one of claims 1 to 3, characterized in that: The steps are: dissolving the fluoride in an organic solvent to obtain a mixed solution; The mixed solution is deposited on the surface of the electron transport layer and annealed to obtain the electron transport layer based on fluoride treatment.

5. The method for preparing an electron transport layer based on fluoride treatment according to claim 4, characterized in that: In the mixed solution, the concentration of fluoride is 0.002-2 mM; The deposition method is spin coating, and the rotation speed is 2000-4000 rpm; The annealing temperature is 100-150° C. and the annealing time is 3-10 minutes.

6. A perovskite solar cell comprising a fluoride-treated electron transport layer according to any one of claims 1 to 5, characterized in that: The invention comprises a substrate, a cathode, an electron transport layer based on fluoride treatment, a perovskite light absorption layer, a hole transport layer and an anode which are stacked in sequence.

7. The perovskite solar cell according to claim 6, characterized in that: The cathode is fixed on the upper surface of the substrate, and the upper surface of the substrate is partially exposed, the fluoride-treated electron transport layer is fixed on the upper surface of the cathode and the exposed upper surface of the substrate, and the upper surface of the cathode is partially exposed, the perovskite light absorption layer is fixed on the upper surface of the fluoride-treated electron transport layer, the hole transport layer is fixed on the upper surface of the perovskite light absorption layer, and the anode is fixed on the upper surface of the hole transport layer.

8. The perovskite solar cell according to claim 6, characterized in that: The substrate and the cathode are integrally formed and are a transparent conductive glass substrate, and the transparent conductive glass substrate is FTO conductive glass, ITO conductive glass or AZO conductive glass; The molecular formula of the material of the perovskite light absorption layer is FA x Cs 1~x PbI3, where 0 < x ≤ 1; the thickness of the perovskite light absorption layer is 300 - 800 nm; The material of the hole transport layer is Spiro-OMeTAD, PTAA, PEDOT:PSS, SAM or P3HT; The material of the anode is metal, and the metal is one or more of gold, silver, and aluminum. The thickness of the anode is 100-150 nm.

9. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The following steps are involved: Step 1: ultrasonically clean the substrate with the cathode using a cleaning agent, deionized water, acetone, isopropanol, and anhydrous ethanol in sequence, and then dry it; Step 2: depositing a solution containing an electron transport layer material onto the surface of the substrate with the cathode after being irradiated by an ultraviolet lamp, and then performing an annealing treatment to obtain an electron transport layer; Step 3: dissolving the fluoride in an organic solvent, depositing the obtained mixed solution on the surface of the electron transport layer in step 2, and then performing annealing treatment to obtain an electron transport layer based on fluoride treatment; Step 4: depositing a perovskite precursor solution on the surface of the fluoride-based electron transport layer in step 3, followed by annealing to obtain a perovskite light absorption layer; Step 5: depositing a solution containing hole transport layer materials on the surface of the perovskite light absorption layer to obtain a hole transport layer; Step 6: Prepare an anode on the surface of the hole transport layer.

10. The method for preparing a perovskite solar cell according to claim 9, characterized in that: In step 1, ultrasonic cleaning is performed in a cleaning agent, deionized water, acetone, isopropanol, and anhydrous ethanol for 20 to 30 minutes respectively; the cleaning agent is conductive glass; In step 2, the ultraviolet light irradiation time is 10 to 30 minutes; In step 2, the concentration of the electron transport layer material in the solution containing the electron transport layer material is 2 to 4 wt %; In step 2, the deposition method is spin coating, the rotation speed is 3000-5000 rpm, the annealing temperature is 150-200° C., and the annealing time is 20-30 min; In step 3, the deposition method is spin coating, the rotation speed is 2000-4000 rpm, the annealing temperature is 100-150° C., and the annealing time is 3-10 min; In step 4, the perovskite precursor solution is deposited on the surface of the fluoride-treated electron transport layer using a one-step anti-solvent method, wherein the anti-solvent is anhydrous ether, chlorobenzene or ethyl acetate; The preparation method of the perovskite precursor solution is as follows: using cesium iodide, formamidine hydroiodide, and lead iodide as solutes, using N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of 4:1 to 6:1 as a mixed solvent, and then stirring at room temperature and in the dark to obtain a perovskite precursor solution; The concentration of the perovskite precursor solution is 0.5 to 1.5 M; The deposition method is spin coating, the rotation speed is 3000-5000 rpm, the annealing temperature is 150-200° C., and the annealing time is 20-30 min; In step 5, the deposition method is spin coating, the rotation speed is 2000-5000 rpm, and the spin coating time is 20-50 s; In step six, the anode is prepared by vacuum evaporation technology.

Citation Information

Patent Citations

  • Ultrahigh-stability and low-cost metal-organic framework materials for efficiently separating acetylene / carbon dioxide and preparation method of ultrahigh-stability and low-cost metal-organic framework materials

    CN113667136A

  • High-stability perovskite solar cell based on co-modification of trifluoroacetic acid organic salt and inorganic salt

    CN115768148A

  • Perovskite solar cell and preparation method therefor

    EP4304317A1

Cited By

  • High-purity villiaumite as well as preparation method and application thereof

    CN122054895A